2020
DOI: 10.1021/jacs.0c09383
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Structure and Reactivity of Fatty-Acid Based (Nano)materials Thanks to Efficient and Scalable 17O and 18O-Isotopic Labeling Schemes

Abstract: Fatty acids are ubiquitous in biological systems and widely used in materials science, including for the formulation of drugs and the surface-functionalization of nanoparticles. However, important questions regarding the structure and reactivity of these molecules are still to be elucidated, including their mode of binding to certain metal cations or materials surfaces. In this context, we have developed novel, efficient, user-friendly, and cost-effective synthetic protocols based on ball-milling, for the 17O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 97 publications
0
22
0
1
Order By: Relevance
“…[101] Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols. [102][103][104][105] But not only liquids have been used as auxiliaries in ball milling reactions, the addition of catalytic amounts of solid ionic salts has also been a common practice. [106] Additionally, silica, alumina, sodium chloride or sodium sulfate rank among the most often used solid additives in ball milling reactions.…”
Section: Gc 5: Safer Solvents and Auxiliariesmentioning
confidence: 99%
See 1 more Smart Citation
“…[101] Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols. [102][103][104][105] But not only liquids have been used as auxiliaries in ball milling reactions, the addition of catalytic amounts of solid ionic salts has also been a common practice. [106] Additionally, silica, alumina, sodium chloride or sodium sulfate rank among the most often used solid additives in ball milling reactions.…”
Section: Gc 5: Safer Solvents and Auxiliariesmentioning
confidence: 99%
“…Moreover, in situ released liquid products in mechanochemical transformations have been observed to accelerate chemical reactions, [100] thus indicating the possibility for LAG catalysis (Figure 4c) [101] . Notably, LAG has also enabled the establishment of practical and economic isotope labelling protocols [102–105] …”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…[7][8][9] Lastly, regarding 17 O labeling, it is only very recently that we demonstrated that the 17 O enrichment of free FAs could be of great interest for (nano)materials science applications, by providing unique insight into the structure of metal soaps and in the surface reactivity of functionalized nano-particles. 10 Despite the great potential that 17 O/ 18 O-labeled FAs could offer to the research community, their use remains scarce compared to 2 H and 13 C labeled species. One of the reasons to this comes from the limited access to 17 O/ 18 O-labeled FAs, which are not commercially available and require to be synthesized.…”
mentioning
confidence: 99%
“…In order to address the need for efficient and scalable 17 O/ 18 O labeling protocols which would be generally applicable to a broad range of FA substrates, we have developed alternative synthetic approaches using mechanochemistry, 12 where the 17 O/ 18 O enrichment is performed at ambient temperature and pressure using only few mL of H 2 O*. 13 Recently, we adapted this methodology for the first time for the synthesis of 17 O and 18 O-labeled oleic and stearic acids, and also scaled-up producing up to 1 g of 17 O-labeled acids for less than 280 h. 10 In this paper, we first demonstrate how by adapting our previous strategy, the scope of 17 O/ 18 O-labeled free FAs can be extended to other saturated FAs with the chain-length varying between C12 to C18 and also to PUFAs containing up to four double bonds, and how detailed analyses of reaction media can help determine working conditions for future syntheses. Then, we demonstrate how an original and efficient labeling scheme based on saponification of the ester derivatives can be used for the 17 O/ 18 O-labeling of the longest and highly sensitive PUFAs with five and six double bonds (EPA and DHA), thereby expanding the scope of approaches for enriching FAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation